Efeito do (NaLix)CO3, COM 0 ≤ x ≤ 2, na sinterização e condutividade elétrica do Ce0,8Gd0,2O1,9 - Grzebielucka, Edson Cezar (Universidade Federal de São Carlos, 2014)
The principles of operation of Solid Oxide Fuel Cells (SOFC) and Molten Carbonate Fuel Cells (MCFC) were merged to create a hybrid device, which can combine the advantages and reduce the disadvantages of both cells, improving the efficiency of energy conversion in stationary power generation devices. Ceria solid electrolytes are among the most promising oxide ion conductors for intermediate temperature SOFC operating at 550-650 °C with high efficiency. However, their major disadvantages is related to Ce4+ to Ce3+ reduction, which occurs at high temperatures and low oxygen partial pressures. Another drawback in using ceria solid solutions is the poor sinterability which requires high temperatures (1400-1600 °C) to achieve high densification (>95 %), makes the manufacturing process costly. Besides, the MCFC exhibits issues such as lifetime due to the corrosive electrolyte formed from the lithium, potassium and sodium carbonates leading to leaks. To improve the characteristics of both cell includes reducing the operating temperature of the device and the sintering temperature of the electrolyte. In the present work, the approach was to reproduce the electrical behavior of composite sintering temperatures at 600 °C, by preparing gadolinium doped ceria (GDC) with lithium and sodium carbonate (MC) samples through oxides mixture. After the electrical behavior reproducibility and the efficiency of the processing method, the effects of sodium carbonate (CS) and MC additions on GDC sintering at higher temperatures than 900 °C were investigated. The sinterability, microstructure and electrical conductivity of pure samples of GDC with CS and MC were evaluated. Composites with 40 % by volume of MC were effective in densifying GDC allowing densification above 95 % for samples sintered at 1200 °C/1 h with total conductivity at 500 °C of 9,26x10-3 S.cm-1, similar to the GDC sintered at 1400 °C/1 h (7,57x10-3 S.cm-1), demonstrating that MC had a positive effect on the densification without compromising electrical conductivity.
Effect of (NaLix)CO3 (0 ≤ x ≤ 2) on sintering and electrical conductivity of Ce0,8Gd0,2O1,9
Keywords: Cerâmica; Céria-gadolínia; Compósitos; Sinterização; Condutividade elétrica; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA